Object-oriented software architecture for NTU_UAV - Balasuriya, Vanoji (2008)
A Object-Oriented software architecture for Autonomous Underwater Vehicles (AUV) is proposed. A real time data logger application is designed and implemented to demonstrate the performance of the proposed architecture.